Design and Experimentation of a Low-Damage Combined Full-Feeding Peanut Picking Device - Jinming Zheng; Shuqi Shang; Ning Zhang; Yao Wu; Xiaochan Wang; Nan Xu (Agriculture)
To address the issues of high pod damage rate and unpicked pod rate in the picking device of peanut picking combine harvesters during the harvesting of sun-dried peanuts, a low-damage peanut picking device was developed. This device combines flat pin teeth with a two-stage round steel concave screen. Contact models between the picking components and peanut pods, as well as between pods and the concave screen, were analyzed to determine the optimal structural parameters of the picking components and the most suitable concave screen type. Using peanut plants that had been dug, windrowed, and naturally sun-dried in the field for 3–5 days as test material, bench tests were conducted with pod breakage rate and unpicked pod rate as evaluation indices. The installation direction of the picking elements and the combination form of the concave screen were used as experimental factors. The optimal configuration was determined to be flat pin teeth installed with parallel axial forward bending with a tip fillet radius of 6 mm, and a concave screen composed of right round steel + straight round steel with front sparse and rear dense type. Field comparative experiments with a conventional picking device—comprising cylindrical bar teeth and a straight round steel concave screen—showed that the pod breakage rate decreased from 1.92% to 1.17%, and the unpicked pod rate decreased from 1.14% to 0.62%. This study provides a theoretical basis for the structural optimization and performance enhancement of the threshing device in peanut picking combine harvesters.